ETNOGRAFI RUMAH ADAT SUKU MAKASSAR DI DESA ALOR KECIL, KECAMATAN ALOR BARAT LAUT, KABUPATEN ALOR; STRUKTUR, FILOSOFI DAN NILAI TRADISI - Ester Prity Claudia Biri; Novriani Kristin Mautang, Naomi Karpada, Norciana Well, Nampi Irayani Blorton, Halena Muna Bekata, R (Adiba Aisha Amira, 2025)
The purpose of this study was to examine the structure, philosophy and traditional values of the Makassar tribe's traditional house in Alor Kecil Village. This research uses qualitative research methods. The technique used for data collection is using interviews, with Mr. Muhammad Nasri Daeng Lanusu as well as observation and documentation. Muhammad Nasri Daeng Lanusu as well as observation and documentation. The results obtained from this study are that the traditional house of the Makassar tribe is a large stilt house, which is made of basic materials of wood, bamboo, and the roof uses zinc. Makassar traditional houses have a roof shape that has a different philosophical meaning from ordinary stilt houses. The traditional house of the Makassar tribe has the traditional value of unity and togetherness.